О влиянии тонкого изотропного покрытия на затухание краевого эффекта при одноосном продольном сжатии слоистого композитного материала - Быстров, В.М. (Видавничий дім "Академперіодика" НАН України, 2008)
The problem of determination of the Saint-Venant end effect in a laminated composite material with thin covering is considered under uniaxial longitudinal pressing of a material. The dependence of the decay length of the end effect on the relation between the surface load period and the structure parameter is investigated. A numerical solution of the boundary-value problem
of elasticity theory of inhomogeneous bodies and the quantitative criterion for the decay of the end effect at normal stresses are used for the analysis of this effect.